Rzeczowniki homograficzne w języku duńskim − analiza morfologiczna i semantyczna - Rajnik, Eugeniusz (Studia Rossica Posnaniensia, 2018)
The article is a study of nouns with the same spelling but different grammatical gender (graphic homonymy, i.e. homography) in Modern Danish. The aim of the article is to analyze the grammatical and lexical homography of both neuter and non-neuter Danish nouns, which have been divided into two groups. The nouns in the first group occur in both grammatical genders with no difference in meaning (grammatical homographs), while the second group is comprised of nouns that do have different meanings based on their grammatical gender (lexical homographs). The author has also identified differences based on word stress (stress homography), different pronunciation and differences connected with the presence of stød or lack thereof, which usually cause a difference in meaning.